Lecturer Response to Violations of Politeness in Student Speech - Megan Asri Humaira; Zahra Fitrah Rajagukguk (Indonesian Journal of Social Research (IJSR), 2020)
The sense of language is reflected in how one communicates. In students, the impression of speaking can be seen from how he communicates as well as communicating with lecturers. However, not a few students do not consider the procedure of communicating with lecturers so as to commit language violations. Whereas the application of impressions in this language should have been a good habit in every individual in communicating and interacting, it is no exception when communicating via WhatsApp chat. This research was conducted to describe how students use language in communicating with lecturers through chat on the WhatsApp messenger app. This research is qualitative research by applying descriptive methods—data obtained using a google form method to lecturers at universities in Indonesia through Whatsapp groups. The results showed that there was suitability of the language used by students towards lecturers and some who committed language violations. Some of the Maxim in the principle of language effect, according to Leech (2016), contained in this study are Maxim wisdom, Maxim appreciation, Maxim simplicity, and Maxim sympathy.